Making Sense of World History - Szostak, Rick (Taylor & Francis, 2021)
"Making Sense of World History is a comprehensive and accessible textbook that helps students understand the key themes of world history within a chronological framework stretching from ancient times to the present day. To lend coherence to its narrative, the book employs a set of organizing devices that connect times, places, and/or themes. This narrative is supported by: Flowcharts that show how phenomena within diverse broad themes interact in generating key processes and events in world history. A discussion of the common challenges faced by different types of agent, including rulers, merchants, farmers, and parents, and a comparison of how these challenges were addressed in different times and places. An exhaustive and balanced treatment of themes such as culture, politics, and economy, with an emphasis on interaction. Explicit attention to skill acquisition in organizing information, cultural sensitivity, comparison, visual literacy, integration, interrogating primary sources, and critical thinking. A focus on historical "episodes" that are carefully related to each other. Through the use of such devices, the book shows the cumulative effect of thematic interactions through time, communicates the many ways in which societies have influenced each other through history, and allows us to compare and contrast how they have reacted to similar challenges. They also allow the reader to transcend historical controversies and can be used to stimulate class discussions and guide student assignments. With a unified authorial voice and offering a narrative from the ancient to the present, this is the go-to textbook for World History courses and students. The Open Access version of this book, available at https://www.taylorfrancis.com/books/9781003013518, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license."